Primer Editorial de la Revista Ginecología y Obstetricia, setiembre 1955 - Molina Navia, Lucas (2016)
I consider it a high honor to the opportunity offered to me by Dr. Lucas Molina, whose intelligence, hard work and enthusiasm the appearance of this journal, write a few words by way of Editorial in the first issue is due. Founded the Peruvian Society of Obstetrics and Gynecology in June 1947, the first presidency held the illustrious late Prof. Constantine J. Carvallo, creator of the current Peruvian gynecological school, it happened then clarified by the obstetrician Dr. Alejandro Busalleu already disappeared and later by very distinguished colleagues, soon he became a general desire edition of its magazine. It was Molina, however, who during his presidency last year had as its leitmotif of this longing and management has become reality.